Nano Revolution: Advancing Civil Engineering through Nanomaterials and Technology - Imoni, Samson; Onyebuchi, Mogbo; Tiza, Michael Toryila; Akande, Ebenezer Ogirima; Onuzulike, Collins (Journal of Novel Engineering Science and Technology, 2023)
Nanomaterials hold immense potential for transforming the field of civil engineering, offering enhanced performance and durability to infrastructure materials. However, their successful implementation faces several challenges and limitations that must be addressed. This abstract highlights the critical challenges associated with nanomaterials in civil engineering, including high production costs, scaling up production, health and safety risks, long-term performance and stability, standardisation and regulation, integration with existing construction practices, lack of comprehensive data and knowledge, and the need for multidisciplinary collaboration. Overcoming these challenges requires optimised manufacturing techniques, safety measures, extensive research, standardised protocols, and cooperation among researchers, engineers, manufacturers, regulators, and policymakers. Addressing these issues will pave the way for the safe and effective utilisation of nanomaterials in civil engineering, unlocking their potential to create sustainable, resilient, and innovative infrastructure systems.